Effectiveness of photodynamic therapy on treatment response and survival of patients with recurrent oral squamous cell carcinoma: a systematic review protocol. Issue 3 (3rd March 2022) - Cardoso, Miguel; Marto, Carlos Miguel; Paula, Anabela; Coelho, Ana Sofia; Pinho e Melo, Teresa M.V.D.; Marques Ferreira, Manuel; Botelho, Maria Filomena; Carrilho, Eunice; Laranjo, Mafalda
ABSTRACT: Objective: This review aims to systematically examine the effectiveness of photodynamic therapy for the treatment of patients with recurrent oral squamous cell carcinoma. Introduction: Oral squamous cell carcinoma is a significant public health problem, and is the seventh most common cancer. Its incidence is mainly due to tobacco use, alcohol consumption, and HPV infection. The survival rates are poor due to diagnosis at advanced stages, with high recurrence rates. Although current evidence does not point to photodynamic therapy as a first-line option, this treatment might be suitable for treating recurrent stages of the cancer where conventional treatments were ineffective. Despite the potential of photodynamic therapy, there is a need to verify the scientific evidence to support its indication for the treatment of recurrent oral squamous cell carcinoma. Inclusion criteria: This review will consider studies on any stage of recurrent oral squamous cell carcinoma treated with photodynamic therapy after receiving first-line conventional treatments. Patients of any age, gender, and geographic location will be included. The primary outcomes will be to evaluate response to treatment, focusing on remission, recurrence, change in size of the lesion, alleviation of symptoms, and survival. Secondary outcomes will be postoperative complications, presence of necrosis, patient quality of life after treatment, and patient satisfaction. Methods: Studies will be searched using a combination of index terms and keywords in MEDLINE, Cochrane Central, Web of Science, Embase, and ClinicalTrials.gov. No date limits will be applied. Articles written in English, French, Spanish, or Portuguese will be considered. Findings will be provided as a narrative synthesis, structured around the photodynamic therapy protocol used. A meta-analysis is planned and subgroup analysis will be conducted if possible. The certainty of findings will be assessed. Systematic review registration number: PROSPERO CRD42020141075